2006
DOI: 10.1177/194589240602000122
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A, Properdin, Complement 3, and Toll-Like Receptors are Expressed Locally in Human Sinonasal Tissue

Abstract: These studies indicate that sinonasal mucosa expresses genes involved in innate immunity including the TLRs and proteins involved in complement activation. We hypothesize that local production of complement and acute phase proteins by airway epithelium on stimulation of innate immune receptors may play an important role in host defense in the airway and, potentially, in the pathogenesis of CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 41 publications
2
72
1
6
Order By: Relevance
“…14,15 The disease entities in this study, CRS with and without nasal polyps, were both characterized by diminished expression of genes involved in epithelial barrier function when compared with control tissue. Prior studies of sinonasal mucosa have shown expression of host defense molecules, such as toll-like receptors, in the sinonasal epithelium 27,28 but their contributions to epithelial damage in tissue from patients with CRS is unknown and likely to be indirect. Similar to findings in the bronchial epithelium in asthma, the epithelium in nasal polyps has shown varying degrees of desquamation, unrelated to the presence of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The disease entities in this study, CRS with and without nasal polyps, were both characterized by diminished expression of genes involved in epithelial barrier function when compared with control tissue. Prior studies of sinonasal mucosa have shown expression of host defense molecules, such as toll-like receptors, in the sinonasal epithelium 27,28 but their contributions to epithelial damage in tissue from patients with CRS is unknown and likely to be indirect. Similar to findings in the bronchial epithelium in asthma, the epithelium in nasal polyps has shown varying degrees of desquamation, unrelated to the presence of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…SAA has multiple potential receptors (formyl peptide receptor-like-1 [FPRL1], receptor for advanced glycosylation end products [RAGE], and TLR2) expressed on many different cells (e.g., macrophages, dendritic cells, neutrophils, and epithelial cells) through which it can participate in innate immune responses with pleiomorphic effects depending on the pathobiologic context (15,22,(41)(42)(43). SAA was shown to activate TLR2 signaling in transfected HeLa cells expressing TLR2 (22).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study also demonstrate a significant increase in the expression of TLR2, TLR4, and TLR7 in nasal polyp tissues from CRSwNP compared to that in nasal mucosal tissues from control subjects and CRSsNP. Previous experimental and clinical studies have suggested that the overexpression of certain TLRs can lead to a more robust immune response to commensal bacteria [17] [18] [21]. In addition, TLR9 expression has been observed to be upregulated in nasal polyps [18].…”
Section: Discussionmentioning
confidence: 93%